On Becoming a Teacher - Kearney, Edmund M.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Students deserve great teachers and learning to become a great teacher is a lifelong journey. On Becoming a Teacher guides both the new and experienced teacher through the exhilarating process of learning to educate students in a way that makes a lasting impact on their lives. Dr. Kearney leads the reader through the process of understanding what lies at the foundation of great teaching, loading each essay with ready-for-classroom use applications and challenging ideas. This book is designed to encourage the reader to think deeply about all aspects of education, while instilling, or rekindling, the excitement, enthusiasm, and teaching excellence shared by all great teachers. Written in conversational essay form and supplemented with discussion and reflection questions, this brief book would make an ideal classroom text for student teaching and education seminars. Whether you aspire to teaching excellence at the elementary school, middle school, high school, or collegiate level, On Becoming a Teacher is a must read. Author Bio: Edmund M. Kearney, Ph.D. is Professor of Psychology at Lewis University. Dr. Kearney has won numerous teaching awards over the past 20 years, including being named the (3z(BTeacher of the Year(3y (Bat the Chicago School of Professional Psychology, the Lasallian Educator of the Year for teaching excellence at Lewis University, and the St. Miguel Febres Cordero Award winner for excellence in scholarship at Lewis University. Dr. Kearney$1 (Bs specialty areas in psychology include cognition, special education, child and adolescent assessment, and the scholarship of teaching and learning.s
Keywords: Education; Education; Education (general).